PENINGKATAN KEMAMPUAN GURU DALAM PENGELOLAAN PEMBELAJARAN TEMATIK MELALUI SUPERVISI KUNJUNGAN KELAS DI SDN 5 BARAN MELINTANG SEMESTER 1 TAHUN PELAJARAN 2019/2020 - Masyabi, Masyabi (JGK (Jurnal Guru Kita), 2020)
Abstract: Improving Teacher Ability in Thematic Learning Management through Supervision of Class Visits at Elementary School 5 Baran Melintang Semester 1. Academic Year 2019/2020 In carrying out their duties as supervisors, school supervisors can choose the right approach according to the problems faced by the teacher. Supervision is not narrowly defined as the best way to be applied in all situations but needs to pay attention to individual abilities, needs, interests, individual maturity levels, personal characteristics of teachers, all of which are considered to apply supervision. The aim is to improve the ability, understanding, and develop thematic learning management strategies for teachers at SDN 5 Baran Melintang, Baran Melintang District. The research subjects are as many as 7 teachers. The technique of collecting data through observation and documentation techniques. As for the descriptive qualitative data analysis in this study is to interpret the data by comparing the results from before the action is taken and according to the action. This data analysis was carried out during the reflection stage. The results of the analysis were used as material for reflection to carry out further planning in the next cycle. The results of data analysis showed that there was an initial condition that only reached an average number of 52.50 with insufficient criteria, increasing to 70.63 with sufficient criteria, and in the last cycle it became 86.88 with very good criteria, and individually per teacher in the initial condition there were no teachers who were declared complete, increasing to 4 teachers or 42.86% and in the last cycle to 7 teachers or 100%. From the explanation above, it can be concluded that the implementation of classroom visit supervision is proven to be able to improve the ability of teachers in managing thematic learning at SDN 5 Baran Melintang, Merbau Island District, Semester 2 of the 2019/2020 Academic Year. Keywords: Improvement, Management, Supervision, Thematic Abstrak: Peningkatan Kemampuan Guru Dalam Pengelolaan Pembelajaran Tematik Melalui Supervisi Kunjungan Kelas Di Sdn 5 Baran Melintang Semester 1. Tahun Pelajaran 2019/2020. Dalam menjalankan tugas sebagai supervisor, pengawas sekolah dapat memilih pendekatan yang tepat sesuai dengan masalah yang dihadapi guru. Supervisi tidak didefinisikan secara sempit sebagai satu cara terbaik untuk diterapkan disegala situasi melainkan perlu memperhatikan kemampuan individu, kebutuhan, minat, tingkat kematangan individu, karakteristik personal guru, semua itu dipertimbangkan untukmenerapkan supervisi. Adapun tujuannya adalah untuk meningkatkan kemampuan, pemahaman, dan mengembangkan strategi pengelolaan pembelajaran tematik bagi guru-Gurudi SDN 5 Baran Melintang Kecamatan Baran Melintang .Subjekpenelitian sebanyak 7Guru. Teknik pengumpulan data melalui teknik observasi dan teknik dokumentasi.Adapun analisis data secara deskriptif kualitatif dalam penelitian ini adalah memaknai data dengan cara membandingkan hasil dari sebelum dilakukan tindakan dan sesuadah tindakan. Analisis data ini dilakukan pada saat tahapan refleksi.Hasil analisis digunakan sebagai bahan refleksi untuk melakukan perencanaan lanjut dalam siklus selanjutnya.Hasil analisis data menunjukkan bahwa ada kondisi awal hanya mencapai angka rerata 52,50 dengan kriteria kurang, meningkat menjadi 70,63 dengan kriteria cukup, dan pada siklus terakhir menjadi 86,88 dengan kriteria baiksekali, dansecara individual per guru pada kondisi awal belum ada guru yang dinyatakan tuntas, meningkat menjadi 4 guru atau 42,86% dan pada siklus terakhir menjadi 7 orang guru atau 100%. Dari penjelasan di atas maka dapat disimpulkan bahwa pelaksanaan supervisi kunjungan kelas terbukti dapat meningkatkan kemampuan Guru dalam pengelolaan pembelajaran tematikdi SDN 5 Baran Melintang Kecamatan Pulau Merbau Semester 2 Tahun Pelajaran 2019/2020. Kata Kunci: Peningkatan, Pengelolaan, Supervise, Tematik